Exploring the antecedents of interdisciplinarity at the European Research Council: a topic modeling approach - Bonaccorsi, Andrea; Melluso, Nicola; Massucci, Francesco Alessandro (Scientometrics, 2022)
The paper applies topic modeling to the collection of ERC-funded proposals, interim reports and related publications, with the aim of measuring in a novel way the degree of interdisciplinarity. This approach helps to address several open research questions about the epistemic, institutional and individual conditions that may favour the blossoming of interdisciplinarity. We present several interesting descriptive data and suggest possible lines of investigation about the antecedents of interdisciplinarity.